The Lunch Conference Diet: Fostering Resident Engagement in Culinary Medicine Through a Curriculum Centered on Changes to Provided Conference Food. Issue 3 (May 2021) - Doxey, Richmond S.; Krug, Michael F.; Tivis, Rick
Background . Despite the burden of chronic disease attributable to lifestyle, most internal medicine residents do not receive adequate training in nutrition and nutrition counseling.Methods . We held a culinary medicine workshop in September 2018, followed by didactic sessions throughout the academic year. Changes were made to lunch conference food to more closely follow the Mediterranean diet and to encourage healthy eating. With a modified NUTCOMP (Nutrition Competence Questionnaire) instrument, we assesses residents' perceived competence with nutrition counseling before and after the curriculum.Results . Twenty-six of 30 residents completed the pre-curriculum and post-curriculum surveys (not the same 26). The mean NUTCOMP score increased from 3.5 to 4.0 ( P < .0001), indicating an increased perceived competence with nutritional counseling. Residents felt that nutritional counseling was important before and after the curriculum (4.2 to 4.3, P = .48). Conference food was more nutritious at the end of the intervention (Mediterranean diet score range 1-4 to 4-7) and residents enjoyed the food more.Conclusions . An innovative, multimodal nutrition curriculum centered on changes to catered lunch conference food improved resident's confidence with nutritional counseling. This could feasibly be integrated into other residency programs with supportive leadership and adequate training.